Digitalisasi Sistem Pengendalian Kualitas Sebagai Upaya Perbaikan Monitoring Data Kualitas Produk Di PT Insera Sena - Michael Andrew Wijaya; Felicia Felicia (Jurnal Titra, 2023)
Digitization can bring benefits to progress in various fields, one of which is themanufacturing industry. PT Insera Sena is a manufacturing company engaged in bicycle production. Producing high-quality products is one of PT Insera Sena's visions, making quality control systems an important aspect in achieving the company's vision. The company's current quality control system is still running manually, so there are several shortcomings that cause problems regarding product quality data monitoring. Data recorded and collected manually stillneeds to be processed into a product quality monitoring report, causing the exchange of data or information to not be done quickly and accurately. To overcome this challenge, PT Insera Sena can enhance their quality control system through digitization. To solve this issue, PT Insera Sena can implement digitalization in their quality control system. This involves creating digitalinspection forms and monitoring dashboards for the Welding, Painting, and Assembly departments. By digitalizing the quality control system, they can monitor product quality data more quickly and make decisions more effectively. Digital transformation in the quality control system can also be a strategic step for the company to carry out continuous improvement.